Inward investment and industrial competitiveness - Margaret Sharp (Intereconomics, 1988)
Inward investment—foreign direct investment in subsidiaries and joint ventures—has played an important part in Europe's post-war development as multinational firms, particularly American multinationals, became a major feature of many European economies. Latterly, we have seen an increasing presence also from Japan and other South-East Asian countries, as well as a resurgence of intra-European investment. What has been the effect of this on the competitiveness of European industry?
Keywords: 330